100 kA/10 kV thyristor stack design for the quench protection system in CRAFT. (1st May 2023) - TONG 仝, Wei 玮; XU 徐, Meng 猛; LI 李, Hua 华; CHEN 陈, Bo 波; SONG 宋, Zhiquan 执权
Abstract: Thyristors have longer lifetimes, higher reliability, and very high voltage and current ratings and they require less maintenance than other high-power semiconductor devices. As a result, they are particularly suitable for quench protection systems (QPSs), which protect the superconducting magnets in large fusion devices from damage. In this paper, we propose a design for a 100 kA/10 kV thyristor stack supported by both theoretical and simulation-based analyses as well as experimental verification. Due to the ultrahigh electrical performance requirements imposed on the QPS by the Comprehensive Research Facility for Fusion Technology (CRAFT), three main issues must be considered: the voltage-balancing problem caused by multiple thyristors in a series structure, the increased junction temperature problem caused by extremely high currents, and the reverse recovery phenomenon that arises from the thyristor's physical structure. Hence, a series of detailed theoretical analyses, simulations, and experiments, including a thyristor junction temperature prediction method and reverse recovery process modeling, were carried out to optimize the design. Finally, the reliability and stability of the thyristor stack were verified by a series of prototype experiments. The results confirmed the correctness and accuracy of the proposed thyristor stack design method and also indicated that the proposed thyristor stack can meet the application conditions of a 100 kA QPS in the CRAFT project.